Comparing cultural content between beginner and intermediate level in Korean language textbooks for Indonesian learners - Johan, Shavira Amelia; Triarisanti, Risa; Lubis, Arif Husein (Universitas Pendidikan Indonesia (UPI), 2024)
Along with the increasing interest in learning the Korean language and culture, textbooks have become important agents in disseminating culture. The cultural value in textbooks plays a crucial role in enhancing learners' cultural awareness. However, there has been limited research specifically examining cultural content in Korean language textbooks for foreigners. Therefore, this study aims to determine the representation of the culture that emerges in the Buku teks Bahasa Korea Terpadu untuk Orang Indonesia at basic and intermediate levels using the categorization of cultural contents from Cortazzi and Jin. This research adopts a qualitative descriptive method by comprehensively analyzing all aspects included, such as vocabulary, grammar, reading, listening, writing, pronunciation, and culture. The findings indicate an uneven distribution of cultural categories. The target culture category dominates with almost three-quarters of the total content, while the source culture category is less represented. The implication is that this study emphasizes the urgency of developing balanced textbooks to enhance equitable cultural awareness among Korean language learners.